SOLDIERS AND DIPLOMATS: INDONESIAN NAVAL DIPLOMACY IN THE SOUTH CHINA SEA - Samy, Muhammad (Indonesian Journal of International Relations, 2023)
Abstract This paper seeks to understand why the Indonesian Navy is utilized as an instrument of diplomacy rather than as war fighters in the South China Sea. The disputes create a threat to Indonesia’s sovereignty and territorial integrity. Historically Indonesia has responded with the use of force in similar situations, however, this is not the case in the South China Sea Disputes. The qualitative method is used in this research in understanding and analyzing the data which is gathered from secondary sources. The theoretical framework used for this research is the national attribute and international system levels of analysis which posits that domestic and international conditions create constraints that affect foreign policy. The research finds that there are several conditions that constrain Indonesia’s response options in the South China Sea disputes and concludes that these constrains cause Indonesia to utilize her navy for diplomacy rather than battle.